Hepatoprotective effect of Rosa canina fruit extract against carbon tetrachloride induced hepatotoxicity in rat - Heibatollah Sadeghi; Abdol Saleh Hosseinzadeh; Mehdi Akbartabar Touri; Mehdi Ghavamzadeh; Mehrzad Jafari Barmak; Hossein Sadeghi; Moslem sayahi (Mashhad University of Medical Sciences, 2016)
Objective: The present study was conducted to investigate the hepatoprotective activity of hydro-ethanolic fruit extract of Rosa canina (R. canina) against carbon tetrachloride (CCl4)-induced hepatotoxicity in rats. Methods: Male Wistar albino rats were randomly divided into six groups of 8 animals of each, including control, toxic (CCl4), R. canina 250, 500, and 750 mg/kg + CCl4 and R. canina 750 mg/kg alone. R. canina (p.o., daily) and CCl4 (1 ml/kg twice a week, 50% v/v in olive oil, i.p.) were administered to animals for six weeks. Serum analysis was performed to assay the levels of aspartate aminotransferase (AST), alanine amino transaminase (ALT), alkaline phosphatase (ALP), albumin (ALB), total protein (TP) and malondialdehyde (MDA). Biochemical observations were also supplemented with histopathological examination (haematoxylin and eosin staining) of liver section.Results: Hepatotoxicity was evidenced by considerable increase in serum levels of AST, ALT, ALP, and lipid peroxidation (MDA) and decrease in levels of ALB and TP. Injection of CCL4 also induced congestion in central vein, and lymphocyte inﬁltration. Treatment with hydro-alcoholic fruit extract of R. canina at doses of 500 and 750 mg/kg significantly reduced CCl4-elevated levels of ALT, AST, ALP and MDA (p